Effects of light intensity and photoperiod on the cultivation of the soft coral Sarcophyton trocheliophorum. (February 2023) - Dong, Ruiguang; Li, Weidong; Wang, Peizheng; Dong, Dengpan; Song, Xiefa; Li, Xian
Abstract: Coral reefs are one of the most diverse, productive ecosystems in the world, and light plays crucial role in its survival. Notably, the effects of light conditions on soft coral and its adaptive mechanism were unclear . Thus, the present study aimed to investigate and evaluate the effects of different light intensities (30, 80 and 130 μmol m −2  s −1 ) and photoperiods (18D:6L, 12D:12L and 6D:18L) on cultivation of soft coral Sarcophyton trocheliophorum . During two 50-day of the experiments, we monitored the zooxanthellae density, Chl a content, enzyme activities (SOD, CAT and GST) and microbial diversity of S . trocheliophorum . Our study's outcomes found that, at the end of the experiment, the 80 μmol m −2  s −1 light intensity group and 12D:12L photoperiod group both possessed the highest zooxanthellae density (2.54 × 10 8  ± 0.14 × 10 8  cells g −1 DW and 2.40 × 10 8  ± 0.07 × 10 8  cells g −1 DW, respectively), Chl a content (295.01 ± 14.13 μg g −1 DW and 287.78 ± 16.13 μg g −1 DW, respectively) and microbial diversity and relatively stable enzyme activities level. Besides, we speculated that the reason for the decline of zooxanthellae density, Chl a content and microbial diversity under other light conditions might be that it induced light stress and caused oxidative damage. The main bacterial composition of S . trocheliophorum in different light conditions was similar at the phylum level, showing the stability of microbial community structure. Proteobacteria, Actinobacteria and Firmicutes were dominant under all light conditions, so we hypothesized that these bacteria phylum play a crucial role in coral growth and survival. In conclusion, compared with the other treatments, 80 μmol m −2  s −1 light intensity and 12D:12L photoperiod were more beneficial to the growth performance of S . trocheliophorum and could be recommended for its cultivation condition. Our study could provide helpful information for sustainable management plans for the cultivation and conservation of soft corals, which was especially important to the protection and restoration of degraded coral reefs. Highlights: The effect of light intensity and photoperiod was observed for the first time on the cultivation of  S. trocheliophorum. The suitable light intensity and photoperiod for the cultivating  S. trocheliophorum  was 80 μmol m −2  s −1  (12D:12L). Light stress was measured by symbiotic zooxanthellae, enzyme activity and diversity of microbial communities of coral. Light stress reduced the number of zooxanthellae and the level of microbial community diversity of S. trocheliophorum.